The catalytic domain of inositol‐1, 4, 5‐trisphosphate 3‐kinase‐a contributes to ITPKA‐induced modulation of F‐actin. Issue 2 (7th February 2015) - Ashour, Dina Julia; Pelka, Benjamin; Jaaks, Patricia; Wundenberg, Torsten; Blechner, Christine; Zobiak, Bernd; Failla, Antonio Virgilio; Windhorst, Sabine
<x xml:space="preserve">Abstract</x> Inositol‐1, 4, 5‐trisphosphate‐3‐kinase‐A (ITPKA) has been considered as an actin bundling protein because its N‐terminal actin binding domain (ABD) induces formation of linear actin bundles. Since in many cancer cell lines ITPKA is essential for formation of lamellipodia, which consist of cross‐linked actin filaments, here we analyzed if full length‐ITPKA may induce formation of more complex actin structures. Indeed, we found that incubation of F‐actin with ITPKA resulted in formation of dense, branched actin networks. Based on our result that ITPKA does not exhibit an additional C‐terminal ABD, we exclude that ITPKA cross‐links actin filaments by simultaneous F‐actin binding with two different ABDs. Instead, stimulated‐emission‐depletion‐microscopy and measurement of InsP3Kinase activity give evidence that that N‐terminal ABD‐homodimers of ITPKA bind to F‐actin while the monomeric C‐termini insert between adjacent actin filaments. Thereby, they prevent formation of thick actin bundles but induce formation of thin branched actin structures. Interestingly, when embedded in this dense actin network, InsP3Kinase activity is doubled and the product of InsP3Kinase activity, Ins(1, 3, 4, 5)P4, inhibits spontaneous actin polymerization which may reflect a local negative feedback regulation of InsP3Kinase activity. In conclusion, we demonstrate that not only the ABD of ITPKA modulates actin dynamics but reveal that the InsP3Kinase domain substantially contributes to this process. © 2015 Wiley Periodicals, Inc.